A2.34 Anti-inflammatory effects of vitamin D are reduced in T-cells from the inflamed joints of rheumatoid arthritis patients. (24th February 2016) - Jeffery, LE; Henley, P; Hewison, M; Filer, A; Sansom, DM; Raza, K
Abstract : Background and objectives: Low serum vitamin D associates with chronic inflammatory diseases such as rheumatoid arthritis (RA), thus vitamin-D supplementation has been suggested for their treatment. T-cells have a pathogenic role in RA. We have shown that active vitamin-D, 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ), has potent anti-inflammatory effects on T-cells. However the efficacy of vitamin-D in an inflammatory setting is unclear. This study was designed to assess the effect of 1, 25(OH)2 D3 upon inflammatory responses by CD4 + T-cells from the blood and synovial fluid (SF) of RA patients. Methods: Ethical approval was granted by Solihull Research Ethics Committee. Patients who fulfilled 1987 ACR criteria for RA and age-matched healthy controls were recruited with informed consent. CD4 + T-cell responses to 100nM 1, 25(OH)2 D3 were assessed by flow cytometry after stimulation. Mononuclear cells from blood and SF were stimulated with antiCD3 and magnetically isolated naïve (CD45-RA) and memory (CD45-RO) CD4 + T cells were stimulated with monocytes+antiCD3. Regulators of 1, 25(OH)2 D3 signalling were measured in purified T-cells by qPCR before and after stimulation with antiCD3/CD28 beads. Significance was tested by Wilcoxon analysis. Results: 1, 25(OH)2 D3 significantly reduced IL-17 and IFNy production by T-cells from the blood of RA patients and healthy controls. By contrast, SF T-cells from RA patients, showed reduced suppression of IL-17 by 1, 25(OH)2 D3 and no inhibition of IFNγ. 98(±1.8)% of SF T-cells were memory compared to 49(±14)% for blood. Unlike SF T-cells, 1, 25(OH)2 D3 suppressed IFNγ production by memory T-cells from blood. However across several targets: IL-17, IFNγ, IL-21, CTLA-4 and FoxP3, naive cells showed greater sensitivity than memory cells to 1, 25(OH)2 D3 . Interestingly, the vitamin D receptor (VDR) was elevated in SF memory T-cells compared to equivalent cells from blood, suggesting that lack of VDR does not explain the diminished responsiveness of SF T-cells. Furthermore, stimulation, increased VDR, RXR and the VDR co-enhancer/co-repressor ratio to similar levels in T-cells from both sites and suppressed their expression of the 1, 25(OH)2 D3 -inactivating enzyme, CYP24A1 equally. Conclusion: Stimulation primes CD4 + T-cells from RA patient blood and SF to respond to 1, 25(OH)2 D3 . However, SF T-cells are less sensitive to 1, 25(OH)2 D3 . This is only partially explained by their shift to memory status. Such insensitivity of joint T-cells to 1, 25(OH)2 D3 has important implications regarding the use of vitamin D to treat RA.